Kidney Transplantation in Semarang: Outcomes and Prognosis - Eriawan Agung Nugroho; Tommy Supit; Ardy Santosa; Nanda Daniswara; Sofyan Rais Addin; Anggun Ari Mukti (Medica Hospitalia : Journal of Clinical Medicine, 2019)
Introduction & objective:Kidney transplantationis increasingly performed acrossIndonesia, including in Semarang. However there are limited publications onrenal transplantationfrom Indonesia, especially from centers outside Jakarta. The objective of this case series is to give a brief overview on the transplantation performed in Semarang, discusscurrent issues and ongoing efforts to address them. Case series:Twenty-seven renal transplants in Dr. Kariadi General Hospital from January2012 until July 2018wereretrospectively analyzed. On average recipients were younger (32.5 years old) compared to the donors (46.8 years old). All kidneys were acquired from living donors with the majority of them to be blood-related(74.1%). The 3 leading etiologies of end-stage renal disease were hypertension (36.0%), diabetes mellitus (26.9%), and autoimmune disease (11.2%). The average total ischemic time was 36.9 minutes andthe average length of stay was 11 days. We report 5 cases of mortality, 3 cases of allograft rejection and no re-transplantation. Discussion: The demographics of kidney transplant patients in Semarang were similar compared to the National data. The limited number of transplant in Semarang contributes to the low number of survival rate and highlights the need of further training and expertise. Better survival rate can be achieved with more transplants number as well as reaching the plateau of learning curve within the coming years. Conclusion: The development of kidney transplant in Semarang follows the National milestones. In order to maximize the potentialthe institution, further improvements should concentrate on the development of integrated organ transplant infrastructure. The main goal of this institution is to establish a solid transplant center capable of covering Central Java, aiding the decentralization of kidney transplant in the Nation Keywords: Kidney transplantation, End-stage Renal Disease, Chronic Kidney Disease, Indonesia, Semarang, Epidemiology, Update